Analysis and Improvement of Chinese Index Technology of Open Source Search Engine Nutch. Issue 2 (March 2019) - Tan, Min; Lan, Hong
Abstract: It is difficult for computer to correctly understand Chinese language, because Chinese is a very complicated language. Therefore, there are many problems existing in Chinese search technology. This paper focuses on solving the defects of Chinese words segmentation technology. Proposes an algorithm which is named as Chinese word segmentation system based on two-way maximum matching. Applies the algorithm into Nutch search engine, testing results shows that the proposed algorithm improved the abilities of Nutch system in Chinese processing.